Reactions of Medicinal Gold(III) Compounds With Proteins and Peptides Explored by Electrospray Ionization Mass Spectrometry and Complementary Biophysical Methods - Massai, Lara; Zoppi, Carlotta; Cirri, Damiano; Pratesi, Alessandro; Messori, Luigi (Frontiers in Chemistry, 2020)
ESI MS is a powerful investigative tool to analyse the reactions of metallodrugs with proteins and peptides and characterise the resulting adducts. Here we have applied this type of approach to four experimental anticancer gold(III) compounds for which extensive biological and mechanistic data had previously been gathered, namely Auoxo6, Au2phen, AuL12, and Aubipyc. These gold(III) compounds were reacted with two representative proteins, i.e. human serum albumin (HSA) and carbonic anhydrase I (hCA I), and with the C-terminal dodecapeptide of thioredoxin reductase. ESI MS analysis allowed us to elucidate the nature of the resulting metal-protein adducts from which the main features of the occurring metallodrug-protein reactions can be inferred. In selected cases mass spectrometry data were integrated and supported by independent 1H NMR and UV-Vis absorption measurements to gain an overall description of the occurring processes. From data analysis it emerges that most of the investigated gold(III) complexes, endowed with an appreciable oxidising character, undergo quite facile reduction to gold(I); the resulting gold(I) species tightly associate to the above proteins/peptides with a remarkable selectivity for free cysteine residues. In contrast, in the case of the less oxidising Aubipyc complex, the gold(III) oxidation state is conserved and a gold(III) fragment still containing the original ligand is found associated to the target proteins. It is notable that the C-terminal dodecapeptide of thioredoxin reductase containing the characteristic -Gly-Cys-Sec-Gly metal binding motif is able in all cases to trigger gold(III) to gold(I) reduction. Our investigation allowed us to identify in detail the nature of the gold fragments that ultimately bind the protein targets and determine the exact binding stoichiometry; some insight on the reaction kinetics was also gained. Notably, a few clear correlations could be established between the structure of the metal complexes and the nature of the resulting protein adducts. The mechanistic implications of these findings are analysed and thoroughly discussed. Overall, the present results set the stage to better understand the real target biomolecules of these gold compounds and elucidate at the atomic level their interaction modes with proteins and peptides.